The economy of medieval Hungary - Laszlovszky, József; Nagy, Balázs (East Central and Eastern Europe in the Middle Ages, 450-1450, 2018)
The Economy of Medieval Hungary is the first concise, English-language volume about the economic life of medieval Hungary. It is a product of the cooperation of specialists representing various disciplines of medieval studies, including archaeologists, archaeozoologists, specialists in medieval demography, historical hydrologists, climate and environmental historians, as well as archivists and church historians. The twenty-five chapters of the book focus on structures of medieval economy, different means and ways of human-nature interactions in production, and offer an overview of the different spheres of economic life, with a particular emphasis on taxation, income and commercial activity. Thanks to its interdisciplinary character, this volume is a basic handbook for the history of economy, production and material culture. Contributors are Krisztina Arany, László Bartosiewicz, Zoltán Batizi, Anna Zsófia Biller, Péter Csippán, László Daróczi-Szabó, Márta Daróczi-Szabó, István Draskóczy, István Feld, László Ferenczi, Erika Gál, Márton Gyöngyössy, István Kenyeres, István Kováts, András Kubinyi, Kyra Lyublyanovics, Árpád Nógrády, Éva Ágnes Nyerges, István Petrovics, Zsolt Pinke, Beatrix F. Romhányi, Katalin Szende, László Szende, Magdolna Szilágyi, Csaba Tóth, and Boglárka Weisz.